Hyponatremia in dogs and cats. Issue 5 (26th August 2019) - Burton, Andrew G.; Hopper, Kate
Abstract: Objective: To review the pathophysiology, diagnostic approach, and treatment recommendations for hyponatremia in dogs and cats. Etiology: Hyponatremia almost always results from an increase in total body water (TBW), and not from loss of sodium. Abnormalities in antidiuretic hormone (ADH) are commonly part of the etiology of hyponatremia. Diagnosis: Diagnosis of hyponatremia focuses on the cause of the increase of TBW. Assessment of the patient's volume status and measurement of urine sodium concentration are important factors. Measurement or calculated estimation of plasma osmolality can also guide the assessment of hyponatremia. Therapy: Too rapid correction of serum sodium can precipitate osmotic demyelination syndrome. As a general rule, serum sodium concentration should be raised ≤10 mmol/L over 24 hours, but rapid increases in serum sodium are indicated if neurologic abnormalities are evident. Serum sodium can be increased using hypertonic saline, with dosing based on the patient's calculated sodium deficit. Treatment of the underlying cause of water ingestion or retention is also required to fully resolve hyponatremia. Prognosis: Mortality rates are significantly higher in dogs and cats with hyponatremia compared to those with normal serum sodium concentrations, even in patients with mild hypontremia (<5 mmol/L below the lower value of the reference interval). Hyponatremia is also associated with increased risk of death if present during specific disease states in dogs.